The Role of Incidental Experiences of Leader Identity for Leaders' Well-Being - Mahoney, Christine Elizabeth (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2025)
This thesis focuses on the phenomenon of incidental leader identity as an understanding that incidental behaviors can shape leader identity. Three studies are presented that enhance our knowledge of incidental leader identity. Study 1 is an exploratory narrative analysis of 61 leadership stories of individuals in the Irish healthcare sector. This research expands our theoretical understanding of the ties between reluctant leadership, helping behavior, influences outside of work, Irish cultural context, and leader identity. As a result of these findings, questions and conditions for future research emerge within these themes. Study 2 explores incidental leader identity as triggered through daily family helping behaviors. We examine the daily implications of helping family behavior in the morning, considering spill-over effects on the workday and back to the home domain in the evening. We integrate leader identity and construal level theory to examine spillover effects throughout the day. Helping family in the morning increases leader identity and associated construal level at work, reducing cognitive resource depletion at the end of the workday and work-family conflict in the home domain after work. Further, we theorize that authentic leadership acts as a person-level moderator that expands the benefits of helping behavior in the home domain. An experience sampling study with multiple measurements across ten working days (N = 175 leaders; N = 1172 days) supports our proposed model. Study 3 extends research on family helping's benefit to leader's well-being by promoting leader identity. Study 3 asks, what type of helping may benefit leaders most - emotional helping or instrumental helping? To answer this focal question, we draw from theories of leader identity and implicit leader theory to propose that gender acts as a person-level moderator that shapes the effect of emotional and instrumental helping for leaders' well-being (i.e., somatic complaints and vigor). In particular, we propose that women benefit more strongly from emotional helping, whereas instrumental helping is more beneficial for male leaders. An experience sampling study with 855 measurements across ten working days with N = 140 leaders suggests that emotional helping family behaviors positively impact leader identity and well-being for female leaders but not their male counterparts. In comparison, we do not find any benefits for instrumental helping behaviors for male and female leaders. This research expands our theoretical understanding of the type of family-helping behavior that spills over into work for female and male leaders but also holds practical implications of what type of morning helping is most beneficial to women leaders. Overall, the three presented studies support a proposition that behaviors can incidentally shape leader identity and associated well-being for leaders. This study offers insights into potential incidental experiences of leader identity and other emerging themes. Studies 2 and 3 of this thesis support a conversation that is helping behaviors positively impact leader identity and family and individual well-being. This research finds that boundary conditions and mediations bind incidental leader identity. In particular, authentic leadership and gender. This thesis adds to the research by introducing incidental leader identity and identifying some of its boundary conditions. Keywords: Leader identity, Incidental leader identity, helping family behavior, family well-being, individual well-being
APPROVED
Keywords: Incidental Leader Identity; Helping Family Behaviour; Family Well-Being; Individual Well-Being; Leader Identity